The structure of Sierras Bayas Group in the north area of the homonymous hills, northwest of Sierras Septentrionales of Buenos Aires, Argentine - Massabie, A.C. (2005)
The Sierras Bayas Group of Late Precambrian age is formed by sedimentary Villa Mónica, Cerro Largo and Loma Negra formations. It is located in the northwest area of Sierras Septentrionales of Buenos Aires Province. The outcrops of this group are located around Olavarría city, mainly in the low isolated hills of Sierras Bayas and also though in a limited way, in the Barker city area. The morphstructure of these sedimentary rocks in the Northern sector of Sierras Bayas is defined by an asymmetric basin subtly tilted to south-southwest. Two interfering fold systems, F1(NE) and F2(NW) which define a type 1 domes and basins pattern, were recognized based on systematic structural mapping of de Sierras Bayas Group formations. Both F1 and F2 foldings with interference angles between 70° to 90° have subvertical axial planes and subhorizontal B axis. In adopted mapping scales, folding systems were observed in three fold orders which exert a direct control over natural an artificial outcrops of the Sierras Bayas Group. The less important local faulting exerts a poor control over the attitude of Late Precambrian folded Sierras Bayas Group and field relationships supports that it's initial activity postdates folding deformation. Ductile deformation of Sierras Bayas Group sedimentary cover, as was locally observed, is thought to be associated with a tectonic reactivation of the basement, Buenos Aires Complex, furnished by pre-existing planar anisotropies of the mylonitized granitic rock mass. The resemblance F1 and F2 patterns of foldings, the overall basin morphostructure and absence of a clear interference sequence between the foldings could be related with a sole episode of constrictional deformation. But also, a type 1 folding interference pattern could have been formed by two regional, orthogonal contractional deformations, in rehologic conditions of low ductility contrast. Folding interference of SBG is considered a result of tectonic activity occurred during Late Precambrian to Lower Early Paleozoic, and predates Cambro - Ordovicic Balcarce Formation of the Sierras Septentrionales. The ductile deformation of Sierras Bayas Group with basement involvement by reactivation of main penetrative anisotropies is correlated with comparable structural patterns owing to Pan African Tectonics, in coetaneous Damara Sequence and Nama Group of Southwest Africa. © 2005 Asociación Geológica Argentina.